2020
DOI: 10.3906/sag-1912-43
|View full text |Cite
|
Sign up to set email alerts
|

The ProFitMap-neck - a questionnaire for measuring symptoms and functional limitations in neck pain: reliability, validity and cross-cultural adaptation of the Turkish version

Abstract: Background/aim: The Profile Fitness Mapping neck questionnaire (ProFitMap-neck) is a reliable and valid assessment instrument for measuring neck-related symptoms and functional limitations in people with neck pain, but a Turkish version of it had not been published. The purpose of this study was to investigate the adaptation, validity, and intrarater reliability of the Turkish version of the ProFitMap-neck. Materials and methods: Two hundred and thirty-five individuals with chronic neck pain were enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
6
5
1
Order By: Relevance
“…Low scores indicate more symptoms and functional limitations. A study confirmed the validity and reliability of the Turkish adaptation of this questionnaire as well [23].…”
Section: Profitmap-neck Questionnairesupporting
confidence: 61%
“…Low scores indicate more symptoms and functional limitations. A study confirmed the validity and reliability of the Turkish adaptation of this questionnaire as well [23].…”
Section: Profitmap-neck Questionnairesupporting
confidence: 61%
“…The present study showed adequate internal consistency of the CHN-ProFitMap-neck (Cronbach’s α > 0.8) [ 31 ], which was consistent with previous studies (the original ProFitMap-neck: Cronbach’s α = 0.88–0.96 [ 16 ]; the Turkish ProFitMap-neck: Cronbach’s α = 0.89–0.960 [ 20 ]; the Brazilian Portuguese ProFitMap-neck (Br-ProFitMap-neck): Cronbach’s α = 0.75–0.76 [ 19 ]).…”
Section: Discussionsupporting
confidence: 91%
“…The present study found good test-retest reliability of the CHN-ProFitMap-neck (ICC = 0.78–0.85). Good test-retest reliability was identified by ICC values (0.78–0.85), which were similar to ICC values in the Turkish study (0.73–0.84) [ 20 ] and the original ProFitMap-neck study (0.80–0.91) [ 16 ], because these studies had a similar interval period (1 week) [ 16 , 20 ]. However, the ICC values were higher in the Br-ProFitMap-neck study (0.97 - 0.98) [ 19 ] because the interval period was much shorter (5 hours), allowing for better control of variables.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations